Evaluation of the growth and tolerance of maize lines under aluminum stress - HERAWATI HERAWATI; MUHAMMAD RIADI; YUNUS MUSA; ROY EFENDI; MUHAMMAD AZRAI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Herawati, Riadi M,MusaY, Efendi R, Azrai M. 2023. Evaluation of the growth and tolerance of maize lines under aluminum stress. Biodiversitas24: 1417-1430. Breeding and utilization of Al-tolerant maize are among the technological applications for preventing a decrease in the growth rate and grain yield of maize in suboptimal fields. This study aimed to determine the growth and production of maize lines under Al stress, obtain maize lines that are tolerant to Al stress, and determine Al absorption in the tested maize lines. This study comprised two steps. In the first step, maize lines were evaluated in acid soils with a pH of 5.12 and an Al saturation of around 22.13%, while the normal condition was carried out on soil with a pH of 6.60 and 0% Al saturation. The study was arranged in a randomized block with three replications. The maize lines used were 24 genotypes consisting of 20 maize lines and four elite lines as a check (Mal 03, CLYN 231, G102612, B11209). In the second step, maize lines were evaluated in the nutrient solution. This study was arranged in a split-plot design with three replications. The main plot was the concentration of Al at three levels, i.e., 0, 7, and 14 ppm. The subplot comprised seven maize lines representing sensitive, medium tolerant, and tolerant categories. They were Pop. A3-1, Pop. A7-1, CB.Pop 10-1-3-1-2-2, CB.Pop 15-4-2-1-1-1, CB.Pop 23-1-2-1-4-2, Mal 03, and G102612. These studies were conducted at the Indonesian Cereal Research Institute, Maros, South Sulawesi, Indonesia, from August 2021 to January 2022. This study showed that Al stress could reduce plant growth by around 10.84% to 50.51% and grain yield by around 62.23% compared to normal conditions. The traits that were significantly correlated with grain yield under Al stress (r>50%), which could be used in maize selection under Al stress, were the number of live plants, ear diameter, number of kernels per row, shelling percentage, SSI, crown Al absorption, and hematoxylin staining. There were two maize lines tolerant to Al stress, namely CB.Pop 11-2-3-4-2-1 and CB.Pop 15-4-2-1-1-1, with potential yields under Al stress conditions of 2.39 t ha-1and 1.59 t ha-1, respectively. Al absorption averages of roots and crowns of Al tolerant maize lines were 159.33 ppm and 36.33 ppm, respectively.